Respuesta :

Answer:

Step-by-step explanation:

Remove the brackets on the left

6p + 5p + 5 = - 8 - 2(p + 12)

Remove the brackets on the right. Be careful this has minus problems.

6p + 5p + 5 = - 8 - 2p - 24

Combine like terms on the left.

11p + 5 = - 8 - 2p - 24

Combine like terms on the right

11p + 5 = - 32 - 2p    

Add 2p on both sides.

11p + 2p + 5= - 32 -2p + 2p

13p + 5 = - 32        

Subtract 5 from both sides. Be careful of the minus.

13p + 5 - 5 = - 32 - 5

13p = - 37  

Divide by 13

13p/13 = - 37/13

p = -2.846

ACCESS MORE